Malocclusion and self-esteem of fourth year high school students of Commonwealth High School Academic Year 2013-2014. - Laroco, Maria Cecilia Y.; Yamat, Jessica Lou S.; Alfaro, Arlene Cecilia A. (Adviser).
INTRODUCTION: It has been conceptualized that the first impression a person makes is based on his appearance which lasts for a long time and that the teeth is perceived to be an important part of the facial appearance. Having a good physical appearance has a positive effect on an individual's self-esteem. Based on such findings, most orthodontists consider having an aesthetic dental appearance. Would lead to a greater self-esteem and social well-being. The aim of this study is to determine whether there is a positive or negative correlation between malocclusion and self-esteem.
METHODS: One hundred fifty one fourth year high school students from Commonwealth High School AY 2013-2014 participated in the study. Self-esteem was assessed by Perceived Need for Treatment, Satisfaction with Dental Appearance, Social Impact of Malocclusion, and Global Negative Self-evaluation Scale (GSE). The participants also underwent oral examination for the dental aesthetic index to assess their malocclusion and corresponding treatment need.
RESULTS: The perceived need for treatment increases as malocclusion increases in severity. The satisfaction with their dental appearance decreases as the severity of malocclusion increases. The social impact of malocclusion increases as the severity of malocclusion increases. The mean self-esteem level as assessed from GSE revealed that participants have slightly high self-esteem level. The mean DAI score was 31.67 which revealed severe malocclusion that recommended treatment is highly desirable.
CONCLUSION: The malocclusion of the fourth year high school students falls under severe malocclusion. This mean score recommends that treatment is highly desirable. The level of self-esteem was interpreted to be slightly high. There was correlation between malocclusion and self-esteem. However, the p-value was marginally significant. There was no statistically significant difference between males and females.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Malocclusion; Self-esteem.; Dental Aesthetic Index (DAI).; Global negative self-evaluation scale